Determinants of Employee Engagement and Productivity: An Analysis of Work Motivation, Competence, Compensation and Transactional Leadership - Agustian Zen (PT FORMOSA CENDEKIA GLOBAL, 2023)
This scientific article aims to show that the variables in the field of human resources offered in this scientific article reinforce through the existing review literature, by looking at and presented in a result of the author's perspective. The recommendation of this scientific article is that it can be continued in this variable can be used by other researchers together into one variable in a research result.